Pemanfaatan Ampas Teh Dan Daun Kelor Sebagai Media Tambahan Dengan Berat Yang Berbeda Untuk Produktivitas Jamur Tiram Putih (Pleurotus ostreatus) - Kartina, Aninda Ayu; , Dra. Suparti M.Si (2017)
Tea dregs contains crude fiber, lignin and cellulose which can be used as an additional medium of white oyster mushroom. While moringa leaves are rich in nutrients that can support the productivity of white oyster mushroom such as amino acids, vitamin B1 (thiamin), nitrogen and cytokinin. The purpose of this study to determine the effect of tea dregs and moringa leaves and the most optimal consentration for white oyster mushroom productivity. This study used completely randomized design (CRD method with two factors and two replications. Factor 1 tea dregs : (T0) without additions, (T1) 50g, (T2) 150g, (T3) 250g. Factor 2 moringa leaves : (K0) without additions, (K1) 50g, (K2) 150g, (K3) 250g. The parameters measured were the time of spread of mycelium,the number of pinhead and edible mushroom pinhead weight. Data were tested by analysis of varians one way ANOVA. Based on the analysis of variance showed that the addition of tea dregs and moringa leaves on the different concentration give significant effect on the time of spread of mycelium,the number of pinhead and edible mushroom pinhead weight. The treatment of K0T3 and K1T2 is the best treatment with a spreading time of 25,5-26 days, pinhead number 19, and wet weight 300 g. Whereas the lowest treatment is K3T0 with a spreading time of 31,5 days, pinhead number 14,75, and wet weight 242,5 g.